PRESENTATION OF FINANCIAL STATEMENTS BASED ON FINANCIAL ACCOUNTING STANDARD OF ENTITIES WITHOUT PUBLIC ACCOUNTABILITY (SAK ETAP) IN THE VILLAGE OWNED ENTERPRISE (BUMDes) MITRA SEJAHTERA ON DECEMBER 2019 (International Journal of Psychosocial Rehabilitation, 2020)
Accounting is very important for companies, especially in financial reporting in which there is information for the company. current government regulations regarding villages, villages must have one product to supplement their income, so a Village Owned Enterprise unit was formed. This BUMDes needs to carry out its tax obligations where the company will need a standard reporting for BUMDes, especially in reporting according to SAK ETAP standards. Information is obtained that BUMDes Mitra Sejahtera Ciburial is a village business unit with ongoing business activities such as Clean Water Management (PAB), PPOB, ATK and Photocopy and Tourism Stalls that are already incorporated, and have carried out business activities but do not yet have financial reporting which is not optimal yet. Based on these conditions and problems, the authors intend to apply financial reporting standards, namely reporting SAK ETAP. Based on the results of the study concluded that the presentation of financial statements in accordance with SAK ETAP can help companies ensure correctly and smoothly so as to minimize the risk of misstatement in the financial statements.